Capital Structure Determinants of Financially Distressed Firms at The Bursa Malaysia. - Izdihar, Baharin @ Md. Daud (2019)
This study provides an insight to the state of determinants of capital structure on financially distressed firms of the Bursa Malaysia, under the classification of Practice Note No. 17 (PN17). This is a quantitative research employing the Partial Least Squares (PLS), a more robust of the Structural Equation Modelling (SEM) variant as its main tools of data analysis. Central to this analysis is the adoption of Central Limit Theorem as its main parameters. The findings of this study concluded that significant determinants for the pre-reorganised capital structure of the PN17 firms are tangibility and size while for the post-reorganized capital structure was growth. In line with conventional wisdom, the relationship between pre-reorganized capital structures and its determinants was only reliable one year prior to the date of reorganization. The study also found that there are no association between the pattern of pre and post reorganized capital structure indicating independence capital structure reorganization process of the PN17 firms. In terms of capital structure models, the pre-reorganized PN17 firms exhibit a preference towards the Total Loan Model which indicated leaning towards financial structure while the post reorganized firms gravitate towards Total Debt Model, indicating the notion of capital structure. This study concluded that the present PN17 classification is effective in fulfilling its duty as intended by Bursa Malaysia in identifying and restructuring financially distress public firms.